Reflection of Bakhtin’s theory into Dostoevsky’s Notes from The Underground, Franz Kafka’s The Metamorphosis: A critical analysis through Dialogism, Dialogic Self-Consciousness, Polyphony and Heteroglossia - Oni, Shazia Azim (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2020.